Ultimate strength prediction of DRM timber beams by plastic approach: Experimental results and discussions - Saleh, Abd. Latif; Abu Bakar, Suhaimi; Mohamed, Zainai; Khin, Maung Zaw (2006)
A new stress model is developed to predict the ultimate bending strength of solid timber beams by using the principle of plasticity. The model predicts the actual bending strength of timber beams from the ratio of ultimate tensile and compressive strengths of the beam material. Standard bending, tension and compression tests are conducted on structural sized specimens to verify the proposed stress model using a local hardwood timber, Dark Red Meranti (DRM). The experimental results of 12 beams, 10 tension specimens and 15 compression specimens are used to verify the proposed model. Test results showed that there is a significant non-linear relationship of the load and the deformation for timber in bending and in compression, but the stress-strain relationship is linear in tension. The strain is linearly distributed across the beam section throughout the test, and the neutral axis shifts towards the tension side when the beam is loaded beyond the proportional limit. Although the tensile strength of timber is larger than its compressive strength, modulus of elasticity (MOE) in tension and compression is approximately the same.